KAJIAN POTENSI EKOWISATA DI DESA LILIBOY KECAMATAN LEIHITU BARAT KABUPATEN MALUKU TENGAH - Biily Seipalla; Lesly Latupapua; Henderina Lelloltery (Jurnal Hutan Tropis, 2020)
The study aims to identify the potential of natural resources as an object and attraction of ecotourism in Liliboy Village, West Leihitu District and to know community perceptions about the potential of ecotourism. The research method used is a survey method by direct observation to the location of attractions and interviews using questionnaires to the community. Data were analyzed using an analysis of the assessment of ecotourism potential carried out by the assessment of natural tourist objects and attractions (ADO), 2000. The five main components of the assessment are attractiveness, accessibility, socio-economic environmental conditions, accommodation and infrastructure and supporting facilities. The results of the study showed that the ecotourism potential in the village of Liliboy was very diverse including the ship's rock beach, waisamal beach and Hatuasa “rafting” river tourism. This tourism potential attracts a number of tourists with various tourist attractions. Community perception shows that 90.0% of respondents agreed to develop ecotourism activities. The community is willing to participate in the development of the tourism object, they argue that if the State of Liliboy becomes a tourist country then they will get job opportunities and business opportunities through various activities such as selling at tourist sites and also becoming a tour guide. The results of the analysis using object assessment and tourist attraction analysis using the ADO guidelines show that the potential attraction of ecotourism objects in Liliboy village is categorized as "Good", with a score of 2320. This shows that the potential of ecotourism in Liliboy village is good for tourism development.